Pure silicon negative electrode for all-solid-state battery and preparation method thereof

By using self-healing adhesive with conductive polymer to form composite adhesive in silicon-based all-solid-state batteries, the structural damage caused by volume expansion during circulation of silicon negative electrode is solved, and the electrochemical performance and cycle stability are improved , extends battery life and improves energy density and safety.

CN119230729APending Publication Date: 2024-12-31HUNAN ENERGY FRONTIERS NEW MATERIALS TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411497130.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Traditional liquid lithium-ion batteries are difficult to achieve higher energy density due to the energy density limitation and safety risks of commercial graphite negative electrodes, and silicon-based all-solid-state batteries are damaged due to volume expansion/contraction during the circulation, making it difficult to achieve stable long cycles.

Method used

Use self-healing binder to form a composite binder and conducting polymer, and combine with pure silicon particles to form three-dimensional network structures and chemical bonds such as hydrogen bonds and covalent bonds to improve the conductivity and mechanical properties of the silicon negative electrode and slow down the volume. Structural damage caused by expansion.

Benefits of technology

It improves the electrochemical performance and cycle stability of the silicon negative electrode, extends the battery life, reduces the content of inactive substances, and improves the energy density and safety of solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230729A_ABST
    Figure CN119230729A_ABST
Patent Text Reader

Abstract

The invention provides a pure silicon negative electrode for an all-solid-state battery and a preparation method thereof, the pure silicon negative electrode comprises a current collector and a coating, the coating comprises a self-healing binder, a conductive polymer and pure silicon particles, and the preparation method comprises the following steps: mixing the self-healing binder with a first solvent to obtain a first glue solution; mixing a conductive polymer with a second solvent to obtain a second glue solution; mixing the first glue solution with the second glue solution to obtain a third glue solution; adding pure silicon particles into the third glue solution and grinding to obtain negative electrode slurry; and combining the negative electrode slurry with a current collector, and performing vacuum drying to obtain the pure silicon negative electrode. The invention can solve the problem that the pure silicon negative electrode of the all-solid-state battery prepared by the existing method is difficult to realize stable long circulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a pure silicon negative electrode for an all-solid-state battery and a preparation method thereof. Background Art

[0002] With the rapid development of the automotive field and energy storage systems, lithium-ion batteries need to move towards higher energy density, higher safety and longer life. However, due to the commercial graphite anode (theoretical energy density of 372mAhg -1 ), conventional liquid lithium-ion batteries face challenges in achieving higher energy density. In addition, these batteries have significant safety risks due to the volatile and flammable liquid electrolyte. To address these issues, solid-state batteries using high-capacity cathode and anode materials have received increasing attention. Silicon is widely considered to be the most promising next-generation lithium-ion battery anode material to replace graphite anodes due to its extremely high theoretical specific capacity, relatively low discharge voltage, abundant natural resources, and environmental friendliness, providing broader possibilities for future development in the silicon field as well as the lithium-ion battery field.

[0003] At present, the silicon negative electrode commonly used in all-solid-state batteries is a composite silicon negative electrode composed of active materials, solid electrolytes, binders and conductive additives in appropriate proportions. The proportion of active materials is relatively low, and the pure silicon negative electrode prepared only using active materials and binders can further improve the energy density. However, during the alloying / de-alloying process, the huge volume expansion / contraction of silicon particles will cause the collapse of the active silicon particle structure and damage to the overall structure of the silicon electrode, which leads to the rapid attenuation of the reversible specific capacity during the cycle, hindering the widespread commercial application of silicon-based all-solid-state batteries. In view of this, it is indeed necessary to propose a new solution to solve the above problems. Summary of the invention

[0004] The purpose of the present invention is to provide a pure silicon negative electrode for an all-solid-state battery and a preparation method thereof, which aims to solve the problem that the pure silicon negative electrode of the all-solid-state battery prepared by the existing method is difficult to achieve stable long-term circulation.

[0005] First, the present invention is implemented like this:

[0006] A pure silicon negative electrode for an all-solid-state battery comprises: a current collector and a coating, wherein the coating comprises a self-healing binder, a conductive polymer, and pure silicon particles.

[0007] Illustratively, the self-healing adhesive includes one or more of polyethylene oxide, polyacrylonitrile, polyvinyl chloride, polyvinylidene fluoride, polyurethane, poly(ether-thiourea), and an adhesive containing a hydroxyl group, a carboxyl group, an amide group, or a ureidopyrimidone group.

[0008] For example, the conductive polymer includes one or more of polyfluorene (PF), polyaniline (PANI), polypyrrole (PPy), polythiophene (PTh), polyethylene dioxythiophene (PEDOT), polyethylene dioxythiophene:polystyrene sulfonate (PEDOT:PSS), and polyacetylene (PA).

[0009] For example, the purity of the pure silicon particles is greater than 99%, and the particle size is 20 nm to 120 nm.

[0010] For example, the mass ratio of the self-healing adhesive to the conductive polymer is 1:(0.333 to 3).

[0011] Next, the present invention is implemented as follows:

[0012] A method for preparing a pure silicon negative electrode for an all-solid-state battery, comprising: mixing a self-healing binder with a first solvent to obtain a first glue; mixing a conductive polymer with a second solvent to obtain a second glue; mixing the first glue with the second glue to obtain a third glue; adding pure silicon particles to the third glue and grinding to obtain a negative electrode slurry; and combining the negative electrode slurry with a current collector and vacuum drying to obtain a pure silicon negative electrode.

[0013] Illustratively, the self-healing adhesive includes one or more of polyethylene oxide, polyacrylonitrile, polyvinyl chloride, polyvinylidene fluoride, polyurethane, poly(ether-thiourea), and an adhesive containing a hydroxyl group, a carboxyl group, an amide group, or a ureidopyrimidone group.

[0014] For example, the conductive polymer includes one or more of polyfluorene (PF), polyaniline (PANI), polypyrrole (PPy), polythiophene (PTh), polyethylene dioxythiophene (PEDOT), polyethylene dioxythiophene:polystyrene sulfonate (PEDOT:PSS), and polyacetylene (PA).

[0015] For example, the first solvent includes one or more of deionized water, N-methylpyrrolidone (NMP), toluene, xylene, n-hexane, cyclohexane, anisole, phenethyl ether, ethanol, dichloromethane, and tetrahydrofuran.

[0016] For example, the second solvent includes one or more of deionized water, N-methylpyrrolidone (NMP), toluene, xylene, n-hexane, cyclohexane, anisole, phenethyl ether, ethanol, dichloromethane, and tetrahydrofuran.

[0017] For example, based on the total mass of the first glue solution, the self-healing adhesive accounts for 10 wt % to 33.33 wt %.

[0018] For example, based on the total mass of the second glue solution, the conductive polymer accounts for 10 wt % to 33.33 wt %.

[0019] For example, the mixing mass ratio of the first glue solution and the second glue solution in the third glue solution is 1:(0.333 to 3).

[0020] For example, the purity of the pure silicon particles is greater than 99%, the particle size is 20 nm to 120 nm, and the solid content in the negative electrode slurry is 90% to 99%.

[0021] For example, the vacuum drying is performed at a temperature of 25° C. to 100° C. and for a time of 0.5 h to 24 h.

[0022] Compared with the prior art, the present invention brings at least one of the following beneficial effects:

[0023] (1) The self-healing adhesive used in the present invention has excellent self-healing ability and mechanical properties, and can effectively repair the mechanical damage of silicon caused by volume change, thereby improving the electrochemical performance of the electrode.

[0024] (2) The conductive polymer used in the present invention can act as both an adhesive and a conductive agent to form a strong conductive bond, provide a charge transfer pathway in a low-cost manner, and improve the conductivity of pure silicon.

[0025] (3) The composite binder formed by the self-healing binder and the conductive polymer can form a three-dimensional network structure, which can slow down the volume expansion of silicon by stress release and enhance the structural stability of the pure silicon negative electrode during the cycle, thereby improving the cycle performance of the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a schematic diagram showing a pure silicon negative electrode for an all-solid-state battery proposed in a first embodiment of the present invention;

[0027] Figure 2 is a flow chart showing a method for preparing a pure silicon negative electrode for an all-solid-state battery according to a second embodiment of the present invention;

[0028] Figure 3 This is a photograph showing the actual pure silicon negative electrode of Example 1. DETAILED DESCRIPTION

[0029] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0030] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0031] Traditional binders, including polyvinylidene fluoride (PVDF), sodium alginate (SA) and styrene-butadiene rubber (SBR), have difficulty in providing sufficient adhesion to accommodate the periodic volume changes of silicon anodes due to weak van der Waals interactions. Linear polymer binders with -COOH, -CN and -OH functional groups can improve interfacial adhesion through hydrogen bonds or chemical bonds, but due to the concentrated mechanical stress on the linear chain, linear polymer binders generally have the disadvantages of insufficient stretchability and poor crack resistance. Therefore, during extreme volume changes, when the mechanical stress exceeds the elastic limit, the lining polymer binder tends to detach from the silicon surface. The present invention imparts good self-healing properties to the silicon anode by introducing a self-healing binder, and provides excellent electron or ion transmission channels to accelerate charge transmission through the properties of the conductive binder that can be used as both a binder and a conductive additive. Specifically, the present invention uses a composite binder formed by a self-healing binder and a conductive polymer, which can improve the volume expansion of silicon-based materials during the charging and discharging process and the problems of pole piece powdering, peeling and instability caused by this factor, thereby improving the conductivity of the silicon negative electrode, improving the mechanical properties of the pole piece, improving the electrochemical properties of the silicon negative electrode, and extending the life of the battery. In addition, the conductive binder can form a hydrogen bond, a covalent bond or a coordination bond with the self-healing binder, which plays a dual stabilizing role on the silicon-based negative electrode and synergistically improves the comprehensive performance of the material.

[0032] The first embodiment of the present invention provides a pure silicon negative electrode for an all-solid-state battery. Figure 1 The device shown includes: a current collector (1) and a coating (2), wherein the coating (2) is combined with the current collector (1), and the coating (2) includes a self-healing binder, a conductive polymer, and pure silicon particles.

[0033] The current collector (1) may include but is not limited to one or more of copper, aluminum, stainless steel, nickel, and carbon; the self-healing adhesive may include but is not limited to polyethylene oxide, polyacrylonitrile, polyvinyl chloride, polyvinylidene fluoride, polyurethane, poly(ether-thiourea), and one or more of adhesives containing hydroxyl, carboxyl, amide, or ureidopyrimidone; the conductive polymer may include but is not limited to one or more of polyfluorene (PF), polyaniline (PANI), polypyrrole (PPy), polythiophene (PTh), polyethylene dioxythiophene (PEDOT), polyethylene dioxythiophene: polystyrene sulfonate (PEDOT:PSS), and polyacetylene (PA). The purity of pure silicon particles may be greater than but not limited to 99%, and the purity is preferably 99.1%, 99.2%, 99.3%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8%, 99.9%, or 100%; the particle size of pure silicon particles may be but not limited to 20nm to 120nm, and is preferably 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, or 120nm.

[0034] The mass ratio of the self-healing binder to the conductive polymer may be, but is not limited to, 1:(0.333 to 3), preferably 1:0.333, 1:0.5, 1:1, 1:2, or 1:3. In addition, the coating (2) may be applied to at least one side of the current collector (1), preferably one or both sides of the current collector (1).

[0035] The second embodiment of the present invention provides a method for preparing a pure silicon negative electrode for an all-solid-state battery, as follows Figure 2 It should be noted that the second embodiment can be used to prepare the pure silicon negative electrode mentioned in the first embodiment, and can also be used to prepare other pure silicon negative electrodes not mentioned; that is, the pure silicon negative electrode mentioned in the first embodiment should not be limited by the content mentioned in the second embodiment.

[0036] First, a self-healing adhesive is mixed with a first solvent to obtain a first adhesive solution. The self-healing adhesive may include but is not limited to polyethylene oxide, polyacrylonitrile, polyvinyl chloride, polyvinylidene fluoride, polyurethane, poly(ether-thiourea), and one or more of an adhesive containing a hydroxyl group, a carboxyl group, an amide group, or ureidopyrimidone, and the first solvent may include but is not limited to one or more of deionized water, N-methylpyrrolidone (NMP), toluene, xylene, n-hexane, cyclohexane, anisole, phenethyl ether, ethanol, dichloromethane, and tetrahydrofuran. Based on the total mass of the first glue solution, the self-healing adhesive may account for, but is not limited to, 10wt% to 33.33wt%, preferably 10wt%, 11.67wt%, 13.33wt%, 15wt%, 16.67wt%, 18.33wt%, 20wt%, 21.67wt%, 23.33wt%, 25wt%, 26.67wt%, 28.33wt%, 30wt%, 31.67wt%, or 33.33wt%. When the self-healing adhesive is mixed with the first solvent, stirring may be used to uniformly mix the two. The stirring method may be, but is not limited to, one or more of paddle stirring, spiral stirring, anchor stirring, magnetic stirring, and ultrasonic stirring; the stirring speed may be, but is not limited to, 800 rpm to 1600 rpm, preferably 800 rpm, 900 rpm, 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm, 1400 rpm, 1500 rpm, or 1600 rpm; the stirring time may be, but is not limited to, 6 h to 12 h, preferably 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, or 12 h.

[0037] Secondly, the conductive polymer is mixed with a second solvent to obtain a second glue solution. The conductive polymer may include but is not limited to one or more of polyfluorene (PF), polyaniline (PANI), polypyrrole (PPy), polythiophene (PTh), polyethylene dioxythiophene (PEDOT), polyethylene dioxythiophene: polystyrene sulfonate (PEDOT:PSS), and polyacetylene (PA), and the second solvent may include but is not limited to one or more of deionized water, N-methylpyrrolidone (NMP), toluene, xylene, n-hexane, cyclohexane, anisole, phenethyl ether, ethanol, dichloromethane, and tetrahydrofuran. Based on the total weight of the second glue solution, the conductive polymer may account for, but is not limited to, 10 wt% to 33.33 wt%, preferably 10 wt%, 11.67 wt%, 13.33 wt%, 15 wt%, 16.67 wt%, 18.33 wt%, 20 wt%, 21.67 wt%, 23.33 wt%, 25 wt%, 26.67 wt%, 28.33 wt%, 30 wt%, 31.67 wt%, or 33.33 wt%. When the conductive polymer is mixed with the second solvent, stirring may be used to uniformly mix the two. The stirring method may be, but is not limited to, one or more of paddle stirring, spiral stirring, anchor stirring, magnetic stirring, and ultrasonic stirring; the stirring speed may be, but is not limited to, 800 rpm to 1600 rpm, preferably 800 rpm, 900 rpm, 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm, 1400 rpm, 1500 rpm, or 1600 rpm; the stirring time may be, but is not limited to, 6 h to 12 h, preferably 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, or 12 h. It should be noted that mixing the self-healing adhesive with the first solvent and mixing the conductive polymer with the second solvent may be performed in different orders according to actual needs; that is, the self-healing adhesive may be mixed with the first solvent first, and then the conductive polymer may be mixed with the second solvent; or the conductive polymer may be mixed with the second solvent first, and then the self-healing adhesive may be mixed with the first solvent; or the self-healing adhesive may be mixed with the first solvent and the conductive polymer may be mixed with the second solvent at the same time.

[0038] Next, the first glue solution is mixed with the second glue solution to obtain a third glue solution. In the third glue solution, the mixing mass ratio of the first glue solution to the second glue solution may be, but is not limited to, 1:(0.333 to 3), preferably 1:0.333, 1:0.5, 1:1, 1:2, or 1:3. When the first glue solution and the second glue solution are mixed, stirring may be used to uniformly mix the two. The stirring method may be, but is not limited to, one or more of paddle stirring, spiral stirring, anchor stirring, magnetic stirring, and ultrasonic stirring; the stirring speed may be, but is not limited to, 1000 rpm to 2000 rpm, preferably 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm, 1400 rpm, 1500 rpm, 1600 rpm, 1700 rpm, 1800 rpm, 1900 rpm, or 2000 rpm; the stirring time may be, but is not limited to, 24 h to 36 h, preferably 24 h, 25 h, 26 h, 27 h, 28 h, 29 h, 30 h, 31 h, 32 h, 33 h, 34 h, 35 h, or 36 h.

[0039] Then, pure silicon particles are added to the third colloid and ground to obtain negative electrode slurry. The purity of pure silicon particles may be greater than but not limited to 99%, and the purity is preferably 99.1%, 99.2%, 99.3%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8%, 99.9%, or 100%; the particle size of pure silicon particles may be but not limited to 20nm to 120nm, preferably 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, or 120nm; in the negative electrode slurry, the solid content of pure silicon particles may be but not limited to 90% to 99%, preferably 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, or 99%.

[0040] Next, the negative electrode slurry is combined with the current collector and vacuum dried to obtain a pure silicon negative electrode. The current collector may include but is not limited to one or more of copper, aluminum, stainless steel, nickel, and carbon. When combining the negative electrode slurry with the current collector, one or more of liquid phase coating, spin coating, screen printing, and 3D printing may be used but is not limited to. The temperature of vacuum drying may be but is not limited to 25°C to 100°C, preferably 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, or 100°C; the time of vacuum drying may be but is not limited to 0.5h to 24h, preferably 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h , 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h, 12h, 12.5h, 13h, 13.5h, 14h, 14.5h, 15h, 15.5h, 16h, 16.5h, 17h, 17.5h, 18h, 18.5h, 19h, 19.5h, 20h, 20.5h, 21h, 21.5h, 22h, 22.5h, 23h, 23.5h, or 24h.

[0041] The present invention is illustrated by the following examples:

[0042] Embodiment 1:

[0043] Weigh 10 mg of polyurethane and 50 mL of deionized water and stir at 1000 rpm for 8 h to obtain glue 1; weigh 10 mg of PEDOT:PSS and 50 mL of deionized water and stir at 1200 rpm for 10 h to obtain glue 2; mix the two glues at a mass ratio of 1:1, at a stirring speed of 1500 rpm, and stir for 24 h to obtain glue 3; add pure silicon particles with a particle size of 30 nm (the solid content in the negative electrode slurry is 96%) to glue 3, and grind them evenly in a mortar to obtain a negative electrode slurry; coat the slurry on the current collector through the liquid phase, and vacuum dry it at 60°C for 12 h to obtain a pure silicon negative electrode, which is as follows Figure 3 shown.

[0044] Embodiment 2:

[0045] Weigh 4 mg of polyethylene oxide and 20 mL of deionized water, stir at 8000 rpm for 8 h to obtain glue 1; weigh 4 mg of PEDOT and 20 mL of deionized water, stir at 1000 rpm for 8 h to obtain glue 2; mix the two glues at a mass ratio of 1:1, at a stirring speed of 1400 rpm, and stir for 28 h to obtain glue 3; add pure silicon particles with a particle size of 60 nm (the solid content in the negative electrode slurry is 98%) to glue 3, and grind evenly with a mortar to obtain a negative electrode slurry; coat the slurry on the current collector through the liquid phase, and vacuum dry at 80°C for 8 h to obtain a pure silicon negative electrode.

[0046] Embodiment 3:

[0047] Weigh 10 mg of polyacrylonitrile and 50 mL of deionized water, stir at 900 rpm for 8 h to obtain glue 1; weigh 10 mg of PANI and 50 mL of NMP, stir at 1000 rpm for 8 h to obtain glue 2; mix the two glues at a mass ratio of 2:1, at a stirring speed of 1800 rpm, and stir for 28 h to obtain glue 3; add pure silicon particles with a particle size of 30 nm (the solid content in the negative electrode slurry is 94%) to glue 3, and grind evenly with a mortar to obtain a negative electrode slurry; spray the slurry on the current collector and vacuum dry it at 70°C for 10 h to obtain a pure silicon negative electrode.

[0048] Embodiment 4:

[0049] Weigh 10 mg of polyvinyl chloride and 50 mL of xylene, stir at 800 rpm for 8 h to obtain glue 1; weigh 10 mg of PPy and 50 mL of NMP, stir at 1000 rpm for 8 h to obtain glue 2; mix the two glues at a mass ratio of 2:1 and a stirring speed of 1200 rpm for 32 h to obtain glue 3; add pure silicon particles with a particle size of 30 nm (the solid content in the negative electrode slurry is 98%) to glue 3, and grind evenly with a mortar to obtain a negative electrode slurry; screen-print the slurry on the current collector, and vacuum dry it at 60°C for 12 h to obtain a pure silicon negative electrode.

[0050] Embodiment 5:

[0051] Weigh 10 mg of polyvinylidene fluoride and 50 mL of deionized water, stir at 1000 rpm for 8 h to obtain glue 1; weigh 10 mg of PEDOT:PSS and 50 mL of deionized water, stir at 1000 rpm for 8 h to obtain glue 2; mix the two glues at a mass ratio of 1:2, at a stirring speed of 1600 rpm, and stir for 24 h to obtain glue 3; add pure silicon particles with a particle size of 30 nm (the solid content in the negative electrode slurry is 95%) to glue 3, and grind evenly with a mortar to obtain a negative electrode slurry; coat the slurry on the current collector through the liquid phase, and vacuum dry at 80°C for 16 h to obtain a pure silicon negative electrode.

[0052] Comparative Example 1:

[0053] Weigh 4 mg of polyethylene oxide and 20 mL of deionized water, stir at 8000 rpm for 8 h to mix evenly to obtain a glue solution; add pure silicon particles with a particle size of 60 nm (the solid content in the negative electrode slurry is 98%) to the glue solution, and grind evenly using an agate mortar to obtain a negative electrode slurry; coat the slurry on the current collector through the liquid phase, and vacuum dry it at 80°C for 8 h to obtain a pure silicon negative electrode.

[0054] Comparative Example 2:

[0055] Weigh 10 mg of polyvinyl chloride and 50 mL of deionized water, stir at 900 rpm for 8 h to mix evenly to obtain a glue solution; add pure silicon particles with a particle size of 30 nm (the solid content in the negative electrode slurry is 94%) to the glue solution, grind evenly to obtain a negative electrode slurry; spray the slurry on the current collector, and vacuum dry it at 70°C for 10 h to obtain a pure silicon negative electrode.

[0056] Comparative Example 3:

[0057] Weigh 10 mg of polyurethane and 50 mL of deionized water, stir at 1000 rpm for 8 h to mix evenly to obtain a glue solution; add pure silicon particles with a particle size of 30 nm (the solid content in the negative electrode slurry is 96%) to the glue solution, and grind evenly with a mortar to obtain a negative electrode slurry; coat the slurry on the current collector through the liquid phase, and vacuum dry it at 60°C for 12 h to obtain a pure silicon negative electrode.

[0058] Comparative Example 4:

[0059] Weigh 10 mg of PEDOT:PSS and 50 mL of deionized water, stir at 1200 rpm for 10 h to mix evenly to obtain a glue solution; add pure silicon particles with a particle size of 30 nm (the solid content in the negative electrode slurry is 96%) to the glue solution, and grind evenly with a mortar to obtain a negative electrode slurry; coat the slurry on the current collector through the liquid phase, and vacuum dry it at 60°C for 12 h to obtain a pure silicon negative electrode.

[0060] Solid-state full batteries were made in the same manner using the negative electrode sheets prepared in Examples 1 to 5 and Comparative Examples 1 to 4, respectively. The electrolyte of the solid-state full battery was Li6PS5Cl, and the positive electrode was NCM811.

[0061] Solid-state full-battery electrochemical performance test parameters: the operating voltage range is set to 2.5V to 4.3V, and the cycle test is carried out using constant current charge and discharge, and the test temperature is 25°C.

[0062] (1) First coulombic efficiency test: the test current is 0.1C, and the first coulombic efficiency (%) of the solid-state battery at 0.1C is obtained. The first coulombic efficiency (%) of the solid-state battery at 0.1C = 0.1C first discharge specific capacity / 0.1C first charge specific capacity × 100%.

[0063] (2) 100-cycle cycle performance test: the test current was 0.5C, and the battery was cycled at 0.5C for 100 cycles to obtain the solid-state battery’s 0.5C first discharge specific capacity and 0.5C cycle 100-cycle discharge specific capacity. The solid-state battery’s 0.5C cycle 100-cycle capacity retention rate = 0.5C first discharge specific capacity / 0.5C cycle 100-cycle discharge specific capacity × 100%.

[0064] It can be seen from Table 1 that the pure silicon negative electrode prepared in Examples 1 to 5 exhibits a higher first-cycle coulombic efficiency and a relatively stable capacity retention rate. Further comparing Comparative Example 1 with Example 2, it can be seen that the self-healing binder polyethylene oxide alone cannot maintain the complete structure of the pole piece, and a short circuit occurs; further comparing Comparative Example 2 with Example 3, the conductive polymer polyethylene dioxythiophene: polystyrene sulfonate (PEDOT:PSS) alone cannot provide conductivity, and the first-cycle coulombic efficiency performance is lower than that of the composite binder. Overall, the composite binder and the self-healing binder prevent Si nanoparticles from crushing, while the conductive polymer provides a fast electronic connection for the entire electrode. The two form a three-dimensional network structure that slows down the volume expansion of silicon by stress release, and enhances the structural stability of the pure silicon negative electrode during the cycle. This stretchable and conductive binder design can reduce the content of inactive substances and increase the proportion of active materials in the negative electrode.

[0065] It can be seen from Table 1 that by comparing comparative examples 3 and 4 with the embodiment, the composite binder composed of the self-healing binder polyurethane and the conductive polymer PEDOT:PSS provides superior first-cycle coulombic efficiency and 100-cycle capacity retention rate compared to the binder composed of the self-healing binder polyurethane and the conductive polymer PEDOT:PSS alone, indicating that the combined effect of the self-healing binder and the conductive polymer will cause unexpected improvements in the first-cycle coulombic efficiency and long-cycle performance of the solid-state battery.

[0066] Table 1

[0067] First cycle coulomb efficiency (%) 100-cycle capacity retention rate (%) Example 1 82.1 77 Example 2 80.3 74 Example 3 81.5 75 Example 4 80.8 73 Example 5 79.6 76 Comparative Example 1 75.9 Short Circuit Comparative Example 2 76.4 45 Comparative Example 3 73.8 Short Circuit Comparative Example 4 77.5 57

[0068] The above contents involving common knowledge are not described in detail, and those skilled in the art can understand them.

[0069] The above descriptions are only some specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included in the protection scope of the present invention. The technical scope of the present invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A pure silicon negative electrode for an all-solid-state battery, characterized in that: include: A current collector and a coating comprising a self-healing binder, a conductive polymer, and pure silicon particles.

2. The pure silicon negative electrode for an all-solid-state battery according to claim 1, characterized in that: The self-healing adhesive includes one or more of polyethylene oxide, polyacrylonitrile, polyvinyl chloride, polyvinylidene fluoride, polyurethane, poly(ether-thiourea), and adhesives containing hydroxyl, carboxyl, amide, or ureidopyrimidone.

3. The pure silicon negative electrode for an all-solid-state battery according to claim 1, characterized in that: The conductive polymer includes one or more of polyfluorene (PF), polyaniline (PANI), polypyrrole (PPy), polythiophene (PTh), polyethylene dioxythiophene (PEDOT), polyethylene dioxythiophene:polystyrene sulfonate (PEDOT:PSS), and polyacetylene (PA).

4. The pure silicon negative electrode for an all-solid-state battery according to claim 1, characterized in that: The purity of the pure silicon particles is greater than 99%, and the particle size is 20nm to 120nm.

5. The pure silicon negative electrode for all-solid-state battery according to claim 1, characterized in that: The mass ratio of the self-healing adhesive to the conductive polymer is 1:(0.333 to 3).

6. A method for preparing a pure silicon negative electrode for an all-solid-state battery, characterized in that: include: Mixing the self-healing adhesive with the first solvent to obtain a first adhesive solution; Mixing the conductive polymer with a second solvent to obtain a second glue solution; Mixing the first glue solution with the second glue solution to obtain a third glue solution; adding pure silicon particles to the third colloid solution and grinding to obtain a negative electrode slurry; as well as The negative electrode slurry is combined with a current collector and vacuum dried to obtain a pure silicon negative electrode.

7. The method for preparing a pure silicon negative electrode for an all-solid-state battery according to claim 6, characterized in that: The self-healing adhesive includes one or more of polyethylene oxide, polyacrylonitrile, polyvinyl chloride, polyvinylidene fluoride, polyurethane, poly(ether-thiourea), and adhesives containing hydroxyl, carboxyl, amide, or ureidopyrimidone.

8. The method for preparing a pure silicon negative electrode for an all-solid-state battery according to claim 6, characterized in that: The conductive polymer includes one or more of polyfluorene (PF), polyaniline (PANI), polypyrrole (PPy), polythiophene (PTh), polyethylene dioxythiophene (PEDOT), polyethylene dioxythiophene:polystyrene sulfonate (PEDOT:PSS), and polyacetylene (PA).

9. The method for preparing a pure silicon negative electrode for an all-solid-state battery according to claim 6, characterized in that: The first solvent includes one or more of deionized water, N-methylpyrrolidone (NMP), toluene, xylene, n-hexane, cyclohexane, anisole, phenethyl ether, ethanol, dichloromethane, and tetrahydrofuran.

10. The method for preparing a pure silicon negative electrode for an all-solid-state battery according to claim 6, characterized in that: The second solvent includes one or more of deionized water, N-methylpyrrolidone (NMP), toluene, xylene, n-hexane, cyclohexane, anisole, phenethyl ether, ethanol, dichloromethane, and tetrahydrofuran.

11. The method for preparing a pure silicon negative electrode for an all-solid-state battery according to claim 6, characterized in that: Based on the total mass of the first glue solution, the self-healing adhesive accounts for 10wt% to 33.33wt%.

12. The method for preparing a pure silicon negative electrode for an all-solid-state battery according to claim 6, characterized in that: Based on the total mass of the second glue solution, the conductive polymer accounts for 10 wt % to 33.33 wt %.

13. The method for preparing a pure silicon negative electrode for an all-solid-state battery according to claim 6, characterized in that: The mixing mass ratio of the first glue solution and the second glue solution in the third glue solution is 1:(0.333 to 3).

14. The method for preparing a pure silicon negative electrode for an all-solid-state battery according to claim 6, characterized in that: The purity of the pure silicon particles is greater than 99%, the particle size is 20nm to 120nm, and the solid content of the pure silicon particles in the negative electrode slurry is 90% to 99%.

15. The method for preparing a pure silicon negative electrode for an all-solid-state battery according to claim 6, characterized in that: The vacuum drying is carried out at a temperature of 25° C. to 100° C. and for a time of 0.5 h to 24 h.

Citation Information

Cited By

  • Negative plate, preparation method and battery

    CN122000290A